Age and the level of acceptance of illnesses by patients with viral hepatitis of type c - Kaźmierczak, Justyna; Kochman, Dorota (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2019)
Introduction Most cases of hepatitis C affect patients between 20 and 40 years of age. This disease is a major diagnostic challenge due to the its insidious course. Aim The aim of this study is to analyse the quality of life of patients with hepatitis C, conditioned by the patient’s age. Material and methods The research was conducted among 101 people. The study used the estimation method and the diagnostic survey, the survey technique, while the tools used in the work are a standardized WHOQOL-Bref question¬naire. Results The age of the respondents did not remain in a statistically significant correlation with the results of quality of life and its subscales (p> 0.05). Conclusions The advanced age had impact on the lower level of quality of life of Hepatitis C patients